Assessment of the effect of tenoxicam in TMJ arthrocentesis - Khalil Ahmed Mohammed Alkamel; Mohammed Hassan Ahmed; Mostafa Kamal Ezz (Cairo : Khalil Ahmed Mohammed Alkamel, 2012)
The turning point in the treatment of TMJ internal derangement was the introduction of TMJ arthrocentesis. To enhance the outcome of arthrocentesis, post operative intra-articular injection of various substances were used. The aim of this study was to evaluate the clinical response to single needle arthrocentesis with intra-articular injection of tenoxicam in relation to the improvement in VAS, MMO, lateral movement, and joint sound in patient with TMJ ID
Thesis (M.Sc.) - Cairo University - Faculty of Oral and Dental Medicine - Department of Oral and Maxillofacial Surgery
Issued also as CD
Keywords: Arthrocentesis; Temporomandibular joint; Tenoxicam